First Candida auris Outbreak during a COVID-19 Pandemic in a Tertiary-Care Center in Lebanon - Allaw, Fatima (Pathogens, 2021)
Candida auris is an emerging fungal pathogen considered as a global health threat. Recently there has been growing concern regarding drug resistance, difficulty in identification, as well as problems with eradication. Although outbreaks have been reported throughout the globe including from several Arab countries, there were no previous reports from Lebanon. We herein report the first cases of C. auris infection from the American University of Beirut Medical Center, a tertiary care center in Lebanon describing the clinical features of the affected patients in addition to the infection control investigation and applied interventions to control the outbreak. Fourteen patients with C. auris infection/colonization identified using MALDI-TOF and VITEK 2- Compact system were reported over a period of 13 weeks. Patients were admitted to four separate critical care units. All of them came through the emergency room and had comorbid conditions. Half of the patients were infected with COVID-19 prior to isolation of the C. auris. C. auris was isolated from blood (two isolates), urine (three isolates), respiratory tract (10 isolates) and skin (one isolate). All the patients had received broad spectrum antibiotics prior to isolation of C. auris. Six patients received antifungal treatment, while the remaining eight patients were considered colonized. Environmental cultures were taken from all four units and failed to isolate the organism from any cultured surfaces. A series of interventions were initiated by the Infection Prevention and Control team to contain the outbreak. Rapid detection and reporting of cases are essential to prevent further hospital transmission. A national standardized infection control registry needs to be established to identify widespread colonization.